Implementation Protection Consumer Passenger Jabodebek LRT Transportation at Halim Station According to Constitution - Novita Roy Lubis; Darwati Darwati; Luky Ferdiles (Jurnal Impresi Indonesia, 2024)
One of the advances in transportation technology in Indonesia is Light Rail Transit (LRT), which is one of the most popular means of land transportation. The aim of this research is to implement consumer protection for Jabodebek Halim LRT transportation passengers according to the law. This research uses a sociological juridical method which is included in the descriptive analytical research category with non-random purposive sampling techniques, and the results are evaluated through qualitative analysis. The results of this research discuss consumer protection implemented in LRT transportation services, the responsibility of the Jabodebek LRT for consumer losses and responsibility for the consequences of LRT technical problems which cause delays in departure schedules, material losses or in-material losses based on the provisions of the Law in Number 8 of 1999 concerning Consumer Protection and Law Number 23 of 2007 concerning Railways. Apart from legal products, railway operational operators are responsible for providing minimum service standard operational procedures to consumers at stations and while the LRT is running. This standard covers the safety of a person's life, feeling safe while using LRT transportation, feeling comfortable at the station and during the trip, easy access to ticket purchases, and equal rights as citizens, as well as handling complaints and inconveniences from passengers regarding the services provided.